The Impact of Intellectual trends on the nature of the Economic Structure of Iraq - العبيدي, عبد الجبار محمود; خلف, اسماء طه (Journal of Economics and Administrative Sciences, 2012)
The Impact of Intellectual trends on the nature of the Economic Structure of Iraq